Why the Dialogue of Civilizations Skids? - V. V. Popov (Vestnik MGIMO-Universiteta)
The article explains why two major international projects supported be UNO – Iranian idea of the dialogue of civilizations and Spanish-turkish conception of the alliance of civilizations did not lead to the desired results and didn’t give expected effects.